2011
DOI: 10.1111/j.1440-169x.2010.01236.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adenovirus‐mediated human telomerase reverse transcriptase gene can stimulate cell proliferation and maintain primitive characteristics in bovine mammary gland epithelial cells

Abstract: The human telomerase reverse transcriptase (hTERT) gene has been used to stimulate the proliferation of most types of human cells. The present study was designed to evaluate the feasibility and efficiency of adenovirusmediated hTERT in the proliferation of bovine mammary gland epithelial cells (bMGEs). A plasmid and an adenovirus vector that carried hTERT, namely pEGFP-hTERT and Ad-hTERT, were constructed and transfected into bMGEs, respectively. In order to select the best strategy for stimulating cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The c-myc and caspase-8 genes also remain constant in the transducted cells at early and late passages, which indicated that no major genetic mutations occurred in the transducted cells. 34 The limitations of this study included: (1) the transducted cells were not labeled before injection process; (2) the duration of this study was too short to observe the efficacy and cell proliferation capacity of rAAV-hTERTtransducted cells in the long run; (3) the tumor genes and tumor repression genes, related with the hTERT, were not studied.…”
Section: Discussionmentioning
confidence: 97%
“…The c-myc and caspase-8 genes also remain constant in the transducted cells at early and late passages, which indicated that no major genetic mutations occurred in the transducted cells. 34 The limitations of this study included: (1) the transducted cells were not labeled before injection process; (2) the duration of this study was too short to observe the efficacy and cell proliferation capacity of rAAV-hTERTtransducted cells in the long run; (3) the tumor genes and tumor repression genes, related with the hTERT, were not studied.…”
Section: Discussionmentioning
confidence: 97%
“…Ovine endometrial cell lines immortalized with HPV E6/E7 genes were also shown to retain original cell phenotype (Johnson et al 1999 ). Human cytotrophoblast cells and bovine mammary gland epithelial cells (bMGEs) immortalized with hTERT gene not only showed enhanced lifespan but also retained original parental phenotype (He et al 2011 ; Wang et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive- hLYZ hTERT-bMGEs were obtained under G418 selection, after which the total cell lysates were subjected to SDS-PAGE in 12% polyacrylamide gel. Proteins were transferred onto PVDF membrane (Millipore, USA) and probed with anti- hLYZ (Sigma) and anti-β-actin (AC-15; Sigma) diluted 1 : 100 and 1 : 500, after which secondary antibody (Sigma) was performed at a 1 : 1,000 dilution [ 10 ]. Immunoreactive proteins were detected using an ECL detection system (Amersham, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is necessary to seek a more efficient strategy for mammary cells as nuclei donors to solve this problem. We previously reported an in vitro bovine mammary gland cells model (hTERT-bMGEs) in which an adenovirus vector carrying human telomerase reverse transcriptase (hTERT) was constructed and infected into bovine mammary gland epithelia cells (bMGEs) [ 10 ]. Our results confirmed that the adenovirus disappeared from the hTERT-bMGEs at passage 15 via successive detection of green fluorescent protein (GFP) and Western blot because of the characteristics of the unintegrated adenovirus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation